Pulping of different parts of whole green jute (C. Capsularies) plant by Kraft process (Bangladesh Journal of Scientific and Industrial Research, 2013)
The chemical composition of the top, middle and bottom part of green jute plant (GJP) are not alike, thus the yield and strength properties of the pulp produced may vary if these are pulped separately. The alpha -cellulose content increases, whereas hemi-cellulose, lignin, ash and extractives decrease from top to bottom part of GJP. The Kraft pulp yield and strength properties increases (except tear) from top to bottom part of GJP. The pulp produced from GJP was found to undergo rapid beating in comparison to those of muli bamboo, jute cuttings. This indicates less energy requirement during refining operation of the GJP pulp. Low extractive (pectin) and high alpha-cellulose is favorable for pulping. Bangladesh J. Sci. Ind. Res. 48(2), 105-108, 2013 DOI: http://dx.doi.org/10.3329/bjsir.v48i2.15740